Targeting TCMR-associated cytokine genes for drug screening identifies PPARγ agonists as novel immunomodulatory agents in transplantation - Hu, Lu; Zhang, Xiaohan; Zhang, Weiqi; Jin, Shuai; Zhao, Jie; Zheng, Jianming; Song, Wenli; Shen, Zhongyang (Frontiers in Immunology, 2025)
ObjectiveT cell-mediated rejection (TCMR) remains a significant challenge in organ transplantation. This study aimed to define a TCMR-associated cytokine gene set and identify drugs to prevent TCMR through drug repurposing.MethodsGene expression profiles from kidney, heart, and lung transplant biopsies were obtained from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) between TCMR and non-TCMR groups were identified, and their intersection with cytokine-related genes yielded an 11-gene TCMR-associated cytokine gene set (TCMR-Cs). To evaluate the effectiveness of this gene set, a diagnostic predictive model was constructed using Lasso regression and multivariate logistic regression, with validation in independent datasets. Connectivity Map (CMap) analysis was employed to screen drugs targeting TCMR-Cs. Experimental validation of the identified drug was performed in vitro using T cell activation and Th1 differentiation assays, and in vivo in a mouse skin transplant model with survival analysis.ResultsThe TCMR-Cs exhibited outstanding predictive performance for TCMR, achieving an AUC of 0.99 in the training cohorts and maintaining strong performance in the test cohorts. CMap analysis identified peroxisome proliferator-activated receptor gamma (PPARγ) agonists as potential therapeutic candidates. Experimental validation showed that the PPARγ agonist rosiglitazone significantly suppressed T cell activation and reduced Th1 differentiation in vitro without cytotoxic effects. The combination of rosiglitazone and rapamycin significantly prolonged graft survival.ConclusionsThis study defined a novel TCMR-associated cytokine gene set that effectively predicts TCMR and identified PPARγ agonists, which prevent TCMR and improve graft survival when combined with rapamycin.